Antibacterial activity of Pakistani Beri honey compared with silver sulfadiazine on infected wounds: a clinical trial. (2nd May 2019) - Yousaf, Iram; Ishaq, Irfan; Hussain, Muhammad Barkaat; Inaam, Saima; Saleem, Sidrah; Qamar, Muhammad Usman
Abstract : Objective: To determine the antibacterial activity of Pakistani Beri honey in patients with infected wounds in comparison with silver sulfadiazine. Method: Inpatients with infected wounds at a tertiary care hospital were divided in to three equal-sized treatment groups. In Group A, patients were treated with non-Gamma irradiated Beri honey. In Group B, Gamma irradiated Beri honey was used, and in Group C silver sulfadiazine was used. Treatment was for a period of four weeks. Pus swabs were taken at day zero and weeks one and four of treatment. Bacteria were identified using the analytical profile index system API 20E, 20NE and API Staph and antimicrobial susceptibility was done as per the Clinical and Laboratory Standards Institute 2010 guidelines. Results: A total of 90 patients with wounds (n=90) took part in the trial. Out of 90 wounds, 47% were post-traumatic and 37% were postoperative. Overall, average length, width and depth of Group A patients' wounds were significantly reduced (p<0.0001). Out of 144 pus swabs; 99 and 45 were Gram-negative rods and Gram-positive cocci, respectively. Among these Pseudomonas aeruginosa (n=25) and Staphylococcus aureus (n=38) were the major pathogens. Interestingly, bacterial load gradually decreased from baseline to week four due to non-Gamma irradiated Beri honey. Moreover, both the Gram-negative rods and Gram-positive cocci displayed 100% resistance to commonly used antibiotics; the most effective drugs were carbapenem and vancomycin. Conclusion: Pakistani Beri honey could be used as an alternative therapeutic option for the management of infected wounds.